Contamination status of major mycotoxins in agricultural product and food stuff in Europe. (September 2021) - Luo, Shujuan; Du, Haolan; Kebede, Haftom; Liu, Yang; Xing, Fuguo
Abstract: Food and feed contamination by mycotoxins are extremely common worldwide. Mycotoxins are small-molecular natural products and toxic secondary metabolites mainly produced by filamentous fungi of Aspergillus, Fusarium, Penicillium and Alternaria . They can cause serious carcinogenicity, growth and reproduction toxicity, mutagenicity and genotoxicity, immunotoxicity and neurotoxicity to humans and animals. Agricultural products are susceptible to mycotoxin contamination in both pre- and post-harvest stages. Most European countries have implemented the maximum limits set by the European Union (EU), but there are still various types of contaminated agricultural products and food stuffs which exceed the limits for mycotoxins in the market. Some European countries are major producers and exporters of cereals, but their economies and trade have been severely affected because of contaminated products by mycotoxins in recent decades. Considering the high occurrence and toxicity of mycotoxins, this study summarizes the occurrence of mycotoxins in agricultural products and food stuffs in Europe and related regional reports and investigations in the past decade. This work mainly focuses on deoxynivalenol, T-2 toxin/HT-2 toxin, fumonisins, zearalenone, ochratoxins and aflatoxins in Europe. Among them, deoxynivalenol had the most serious contamination and the widest distribution. T-2 toxin/HT-2 toxin, fumonisins, zearalenone and ochratoxins were basically below the EU limit. Aflatoxin that has attracted worldwide attention was actually low in Europe and less distributed. With constant attention to food safety, European countries have continuously adjusted the maximum limit, established monitoring teams and improved agricultural production methods to protect human health and food trade.